PELATIHAN PENGOLAHAN MAKANAN RINGAN GAPIT DAN STICK BERBAHAN DASAR BAWANG MERAH DI DESA KEPOHKIDUL BOJONEGORO - Nurdiansyah, Denny; Aziz, Su’udin; Hambali, M. Ridlwan; Rahman, Rifqi Maulana; Koniva, Deskia Dwi Nur (Yayasan Education and Social Center, 2024)
There is less than optimal utilization of the red onion harvest, so that many red onions are sold to collectors at standard prices, while some red onions that do not meet the requirements are usually wasted. In addition, there are still many unemployed people in Kepokidul Village, some of whom are directed by the village head to look after the parking lot at the Pedang Reservoir. This reservoir is a potential and motivation for the village SMEs to produce and market processed products. Therefore, KKN UNUGIRI held training on processing processed products from red onions that will become high-value and healthy processed products. The purpose of this Community Service (PkM) is to improve the ability of the village community to produce processed products from red onion raw materials and market them. Thus, creating an increase in the number of SMEs in Kepohkidul Village which reduces unemployment. The target of the training provided was 30 PKK mothers from Kepohkidul Village. The method of implementing PkM was carried out in four activities over three days, namely extracting community knowledge, socialization, training, and evaluating understanding. The results of this PkM activity are an increase in the knowledge and insight of the village community regarding processed red onion products, as well as increasing options for village SMEs for marketed products. The evaluation resulting from this training resulted in 75% of participants experiencing an increase in knowledge and insight related to processed red onion products. The conclusion that can be drawn is that unemployment can be reduced by increasing the number of village SMEs by providing training on processed products and marketing